Any idea why is the sign wrong here:
From $\sum (u \overline{u} - v \overline{v}) = 1$ we have $\sum (u u^+ - v v^+) = \gamma^0$ so that
$Q = \int d^3 x \psi^+ \psi = \int d^3 x \overline{\psi} \gamma^0 \psi = \int \dfrac{d^3 p}{(2\pi)^3} \hat{\overline{\psi}}\gamma^0 \hat{\psi}= \int \dfrac{d^3 p}{(2\pi)^3} \hat{\overline{\psi}}[\sum (u u^+ - vv^+)] \hat{\psi}$
$ \ \ \ = \sum \int \dfrac{d^3 p}{(2\pi)^3} [(\hat{\overline{\psi}}u ) (u^+ \hat{\psi} ) - ( \hat{\overline{\psi}} v ) (v^+ \hat{\psi})]$